ASPM facilitates colorectal cancer cells migration and invasion by enhancing β‐catenin expression and nuclear translocation. Issue 2 (6th November 2021) - Wang, Lu; Hu, Xiao‐Dan; Li, Shou‐Ying; Liang, Xu‐Yang; Ren, Lin; Lv, Sheng‐Xiang
Abstract: Increased abnormal spindle‐like microcephaly (ASPM) expression has been linked to clinical stage and poor prognosis in cancers, but the molecular mechanisms by which ASPM promotes cell metastasis in colorectal cancer (CRC) has not been identified. This study showed that the abilities of cell migration, invasion, and epithelial–mesenchymal transition (EMT) were attenuated in ASPM‐deficient CRC cell lines. Furthermore, we reported that attenuation of ASPM expression inhibited CRC cell metastasis in vivo. Additionally, the expression of ASPM was positively correlated with β‐catenin level in CRC tissues. Mechanistically, ASPM can upregulate β‐catenin transcription by stimulating the β‐catenin promoter and enhancing the nuclear translocation of β‐catenin in CRC cells, which leads to the activation of the Wnt/β‐catenin pathway. Finally, we showed that ASPM effectively induced CRC cell migration and invasion in a β‐catenin‐dependent manner.